FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI CENGKEH DI DESA WAODE BURI KECAMATAN KULISUSU UTARA KABUPATEN BUTON UTARA - Indra Indra; R. Marsuki Iswandi; Abdul Gafaruddin (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2024)
The objective of this study is to ascertain the factors that influence clove production in Waode Buri Village, North Kulisusu District, North Buton Regency.The population of this study consists of all clove farmers in Waode Buri Village, North Kulisusu District, North Buton Regency, which amounts to 460 individuals. The number of research respondents was determined using the Slovin formula with an error rate of 15%, yielding a final sample of 41 respondents.Data collection involved the use of observation, interview, and documentation methods, with the aid of questionnaires.The study's independent variables are factors affecting clove production, including land area, labor, number of productive trees, and plant age.Data analysis was conducted quantitatively using multiple linear regression analysis with the assistance of SPSS software. The findings indicated that the factors influencing clove production in Waode Buri Village, North Kulisusu Subdistrict, were land area (X1), while factors such as labor (X2), number of productive trees (X3), and plant age (X4) exhibited no significant impact on clove production. However, the factors that exerted no influence demonstrated a positive value on clove production.